Chinese classics selections from Lu's commentaries of history - Lu Buwei; Wang Guozhen ([Beijing] China Intercontinental Press, 2017)
Selections from Lu's Commentaries of History is an ancient classic compiled in 239 B.C. by Lu Buwei, the Prime Minister of the state of Qin, who collected and arranged the writings of his ""house guests"" or followers into a book. The writings represented his ideas and aimed to serve as a guide to government for the Qin ruler. Dealing with a wide range of subjects in more than 20(3,000 words, the book is one of the longest of the early Chinese classics and an encyclopedic compendium of early Chinese thought and civilization. This book is edited and translated by the famous translator Wang Guozhen, to introduce Selections from Lu's Commentaries of History to the foreign readers.
Keywords: Folklore -- China; Chinese fiction -- History and criticism. -- Ming Dynasty, 1368-1644.; China -- Social life and customs -- Fiction